The Basoph8 Mice Enable an Unbiased Detection and a Conditional Depletion of Basophils - Pellefigues, Christophe; Mehta, Palak; Prout, Melanie Sarah; Naidoo, Karmella; Yumnam, Bibek; Chandler, Jodie; Chappell, Sally; Filbey, Kara; Camberis, Mali; Le Gros, Graham (Frontiers in Immunology, 2019)
Basophils are granulocytes involved in parasite immunity and allergic diseases, known for their potent secretion of type 2 cytokines. Identifying their functions has proven to be controversial due to their relative rarity and their complex lineage phenotype. Here, we show that the expression of basophils lineage markers CD200R3 and FcεRIα is highly variable in inflammatory settings and hinders basophils identification by flow cytometry across multiple disease states or tissues. Fluorophore-conjugated antibody staining of these lineage markers strongly activates basophil type 2 cytokine expression, and represents a potential bias for coculture or in vivo transfer experiments. The Basoph8 is a mouse model where basophils specifically express a strong fluorescent reporter and the Cre recombinase. Basophils can be identified and FACS sorted unambiguously by their expression of the enhanced yellow fluorescent protein (eYFP) in these mice. We show that the expression of the eYFP is robust in vivo during inflammation, and in vitro on living basophils for at least 72h, including during the induction of anaphylactoid degranulation. We bred and characterised the Basoph8xiDTR mice, in which basophils specifically express eYFP and the simian diphtheria toxin receptor (DTR). This model enables basophils conditional depletion relatively specifically ex vivo and in vivo during allergic inflammation and their detection as eYFP+ cells. In conclusion, we report underappreciated benefits of the commercially available Basoph8 mice to study basophils function